Properties of the Hankel-Hausdorff operator on Hardy space H1 (0,) - Upadhyay S.K.; Debnath L.; Yadav R.N. (My University, 2025)
The main objective of this paper is to introduce the Hankel-Hausdorff operator of a function f generated on the Hardy space and to study its various properties in. © 2012, by Oldenbourg Wissenschaftsverlag, München, Germany. All rights reserved.